Considering service animals in tourism - Rickly, Jillian M. (Elsevier, 2018)
Accessible tourism is a rapidly growing sector of the tourism industry and increasingly recognized as essential to supporting mobility and leisure as human rights (Buhalis & Darcy, 2001; Buhalis, Darcy, & Ambrose, 2012; McCabe & Diekmann, 2015). This has contributed to active research regarding disabilities and mobilities needs in tourism (see Darcy & Dickenson, 2009; Small & Darcy, 2010), as well as the embodied experience of traveling with disabilities (see Small, Darcy, & Packer, 2012). Yet, the ways in which transportation services, accommodations, and tour operators provide for the needs of service animals remains underdeveloped (Pond, 1995; Bourland, 2009; European Commission, 2015) and, indeed, underexamined (see Small, Darcy, & Packer, 2012). Service animals are increasingly utilized to mitigate mobility challenges, particularly for those who live with visual impairment, physical disabilities, disorder response, or require emotional and psychological support. Nevertheless, we lack an understanding of the role of service animals in tourism mobilities and touristic experience (see also Small, Darcy, & Packer, 2012).